A new species of Indigofera (Leguminosae, Papilionoideae) from Misiones with a key to species from Argentina - São-Paulo, Rita De Cássia Alves Menezes; Snak, Cristiane; Ribeiro, Carolina Lima; Rocha, Lamarck; Queiroz, Luciano Paganucci De (Phytotaxa, 2025)
Indigofera stolonifera, a new stoloniferous species from Misiones, Argentina, is described and illustrated. The new species resembles I. campestris but differs in habit (erect stoloniferous herb vs. decumbent subshrub in I. campestris), petiole length (2–2.5 mm vs. 5–6 mm), and leaflet indumentum (sericeous to velutinous vs. pubescent). A detailed description, illustrations, photos, distribution map, and comments on taxonomy and morphology are presented. Additionally, we present an updated identification key for Indigofera species in Argentina.